The impact of climate change on potential rob floods and its effect on regional spatial planning on the Surabaya coast - Okvitasari, Astri Rino; Fatoni, Arrizal R.; Bahtiar, Ahmad; Faridatussafura, Nurzaka; Hermanto, Ady; Aulady, M. Ferdaus N. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Climate change is a global issue that is of concern to the world. One of the impacts of climate change is sea level rise. Rising sea levels can cause tidal floods, especially in coastal areas. Based on data from the Meteorology, Climatology and Geophysics Agency (BMKG), one evidence of climate change is an increase in sea level. Satellite altimetry measurements show a trend of sea level rise in Indonesia from 1992-2022 averaging around 4 mm/year. Rising sea levels have an impact on increasing the frequency of coastal flooding, retreating coastlines, and the disappearance of national borders. The city of Surabaya is one of the coastal cities in Indonesia which has the potential to experience an increase in the height of tidal floods due to climate change. The potential for tidal floods due to climate change could harm the spatial planning of coastal areas in Surabaya. The results of this research show that the coast of Surabaya has a moderate level of tidal flood vulnerability with an area of 8230.77 ha, a high category with an area of 1739.21 ha, and a very high category with an area of 178.13 ha. The area is dominant from most of the coast of the Semampir subdistrict to Benowo and the border of the Bulak and Mulyorejo subdistricts. Tidal floods can cause the submergence of productive lands, such as settlements, fish farms, and warehouses. This can cause economic and social losses for coastal communities. Therefore, adaptation efforts are needed to reduce the impact of tidal floods due to climate change. These adaptation efforts can be carried out through improving spatial planning and environmental planning for coastal areas.